Industrial location and sectoral linkages: the case of the Brazilian automotive industry - Gabriel, Luciano Ferreira (2016)
The aim of this article is to analyse the spatial distribution of the automotive industry in Brazil in terms of its various economic categories between 1995 and 2011, and to shed light on its sectoral linkages through inter-regional input-output matrices. By calculating the coefficient of localization (QLij) for that period, it was found that the third wave of investments, which began in the second half of the 1990s, actually caused a slight spatial deconcentration of this sector in the national economy. The coefficient of geographic association (CAik)calculated for different years revealed a slight reduction, while maintaining a high level of concentration, which suggests that vehicle production is closely integrated with other economic activities. This integration was corroborated particularly in terms of input purchases (backward linkages) in all of the analysed regions.